2012
DOI: 10.1038/ejcn.2012.158
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intake and stroke risk: a meta-analysis of prospective cohort studies

Abstract: Findings of this meta-analysis indicate a significant inverse dose-response relationship between dietary fiber intake and risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…3 This association was present both for soluble and for insoluble fiber, and independent of age, sex, and classic atherogenetic risk factors. This is consistent with a recent metaanalysis by Chen et al 4 on dietary fiber intake and risk of stroke, suggesting no significant difference between sexes.…”
Section: To the Editorsupporting
confidence: 82%
“…3 This association was present both for soluble and for insoluble fiber, and independent of age, sex, and classic atherogenetic risk factors. This is consistent with a recent metaanalysis by Chen et al 4 on dietary fiber intake and risk of stroke, suggesting no significant difference between sexes.…”
Section: To the Editorsupporting
confidence: 82%
“…The midpoints of the upper and lower boundaries of each category were used if the median or mean were not reported. For studies that reported the open upper boundaries or uppermost boundaries closed with extreme value, we assumed the width of the interval to be the same as in the closest category 11. A restricted cubic spline model with four knots set at the 5th, 35th, 65th and 95th centile levels of LTPA was then produced using the generalised least square regression and taking into account the correlation between each set of published RRs 12.…”
Section: Methodsmentioning
confidence: 99%
“…Although results from individual studies on dietary fiber intake in relation to stroke have been inconsistent, 3 meta-analyses have reported an overall significant inverse association (6,19,20). For example, in 2 dose-response meta-analyses, including 6 (19) or 8 (20) studies, the risk of stroke decreased by 7% for every 7 g/d (20) or by 12% for every 10 g/d (19) increment of total fiber intake.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in 2 dose-response meta-analyses, including 6 (19) or 8 (20) studies, the risk of stroke decreased by 7% for every 7 g/d (20) or by 12% for every 10 g/d (19) increment of total fiber intake. Few previous studies have considered potential confounding from other nutrients present in fiber-rich foods.…”
Section: Discussionmentioning
confidence: 98%